2021
DOI: 10.1186/s12889-020-10120-w
|View full text |Cite
|
Sign up to set email alerts
|

Climate-related migration and population health: social science-oriented dynamic simulation model

Abstract: Background Social science models find the ecological impacts of climate change (EICC) contribute to internal migration in developing countries and, less so, international migration. Projections expect massive climate-related migration in this century. Nascent research calls to study health, migration, population, and armed conflict potential together, accounting for EICC and other factors. System science offers a way: develop a dynamic simulation model (DSM). We aim to validate the feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 154 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…For example, Negev et al (58) point out that health systems in sub-Saharan Africa are ill-equipped for additional pressures from climate migrants, given that they are fragmented, experience acute material and human resource shortages, are weakened by decades of underinvestment, and are coping with high rates of infectious diseases and rising rates of noncommunicable diseases. Reuveny (70) develops a hypothetical model of climate-related migration and health and suggests that immigration could lead to situations where local demand for health care exceeds capacity. And Sabasteanski et al (74) argue that there is inadequate policy focus on the health consequences of climate migration, specifically for internal migrants, and health system preparedness.…”
Section: Climate-resilient Health Systemsmentioning
confidence: 99%
“…For example, Negev et al (58) point out that health systems in sub-Saharan Africa are ill-equipped for additional pressures from climate migrants, given that they are fragmented, experience acute material and human resource shortages, are weakened by decades of underinvestment, and are coping with high rates of infectious diseases and rising rates of noncommunicable diseases. Reuveny (70) develops a hypothetical model of climate-related migration and health and suggests that immigration could lead to situations where local demand for health care exceeds capacity. And Sabasteanski et al (74) argue that there is inadequate policy focus on the health consequences of climate migration, specifically for internal migrants, and health system preparedness.…”
Section: Climate-resilient Health Systemsmentioning
confidence: 99%
“…Additionally, through sending remittances back home, climate migrants can support local adaptation and resiliency-building within their communities, improving both social and environmental determinants of health in otherwise climate-vulnerable settings ( International Organization for Migration 2023 ; Musah-Surugu et al., 2018 ; Hassan and Mahmud, 2021 ). With regards to the broader health status of migrant receiving communities, recently developed dynamic simulation models have shown that policies which restrict access to healthcare and environmental health services for climate migrants may harm the net health of all residents ( Reuveny, 2021 ). This lends further justification to the need to support climate-affected migrants in their adaptive relocation pursuits as a means of optimizing the health and well-being of migrants, sending, and receiving communities alike.…”
Section: Migration As Adaptation and The Global Charter For The Publi...mentioning
confidence: 99%
“…The variety of migration models mainly included regression models [2], dynamic simulation models [52], life-course approach [53], decision tree models [54], and eigenfunctionbased spatial filtering approach [22], and so on. In this paper, we adopted the logistic regression model.…”
Section: Logistic Regressionmentioning
confidence: 99%